THE CONCEPT OF H. DUMEIRI ILYAS'S THOUGHT AND SOCIAL CONTRIBUTION IN THE DEVELOPMENT OF ISLAMIC EDUCATIONAL INSTITUTIONS IN LUBUK PAKAM - Agus Riswandi; M. Syukri Azwar Lubis; Muhammad Tohir Ritonga (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2026)
This study examines the role and contribution of H. Dumeiri Ilyas in the development of Islamic educational institutions in Lubuk Pakam, Deli Serdang Regency, and analyzes the concepts, values, and educational practices he developed along with their relevance to present-day Islamic education. A qualitative approach was employed through a descriptive-analytical biographical study design. Data were collected through in-depth interviews, limited participant observation, and document review involving seven purposively selected informants, including family members, institutional administrators, educators, alumni, and academics. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, comprising data reduction, data display, and conclusion drawing, supported by source and method triangulation. The findings reveal three main points. First, H. Dumeiri Ilyas made tangible contributions through three interrelated dimensions: institutional development (an orphanage and madrasah under Al-Jam'iyatul Washliyah), the formation of an Islamic institutional culture, and enhanced social mobility for hundreds of orphans and underprivileged families through access to education. Second, the educational model he pioneered rested on the integration of knowledge and morals, exemplary conduct (uswah hasanah) as the primary pedagogical method, and an orientation toward maximum achievement regardless of students' economic background, representing a concrete expression of the concept of insān kāmil. Third, his intellectual legacy remains principally relevant to contemporary Islamic education and continues to be transmitted through institutional practice, intergenerational personal transmission, and institutional narrative